2015
DOI: 10.1088/1742-6596/602/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and physical-chemical characteristics of the solutions of the medicines

Abstract: Abstract. In the laboratory studied the dynamics of rheology of water solutions with plasmainflammatory and antiseptic funds when mixing them with blood, plasma and pus under the influence of the following physical and chemical factors of local interaction: gravity, specific gravity, temperature, relative viscosity, internal pressure, sparkling water, total concentration of the ingredients, surface activity, volume of acid and osmotic activity of medicines. Found that the rheology of biological liquids improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 1 publication
0
16
0
2
Order By: Relevance
“…Over-the-counter products used for human use are typically sold at 3 percent active ingredient [ 35 , 36 ]. Bleaching of textile products for removal of bloodstains has been thoroughly described in literature [ 37 , 38 , 39 , 40 ]. Most solutions used for bloodstain removal represent aqueous solutions of hydrogen peroxide or its water-soluble source of from 0.01 to 15% in combination with agents maintaining a pH of more than 7.0 at the level of its osmotic activity below 140 mosmol/l and with a local temperature in the range from +26 to +42 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Over-the-counter products used for human use are typically sold at 3 percent active ingredient [ 35 , 36 ]. Bleaching of textile products for removal of bloodstains has been thoroughly described in literature [ 37 , 38 , 39 , 40 ]. Most solutions used for bloodstain removal represent aqueous solutions of hydrogen peroxide or its water-soluble source of from 0.01 to 15% in combination with agents maintaining a pH of more than 7.0 at the level of its osmotic activity below 140 mosmol/l and with a local temperature in the range from +26 to +42 °C.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the cause of Nicolau syndrome is a very strong local irritating effect of medicinal solutions [26]. This became possible because the local irritating effect of drugs on tissues at injection sites is not controlled, as it is not included in the standard of drug quality control [27]. It has been shown that in addition to this, the standard for quality control of medicines does not include an assessment of their osmotic activity [28].…”
Section: Sources Of the Problemmentioning
confidence: 99%
“…Дополнительным достоинством обсуждаемого метода является наличие биоцидных свойств у фтора, медленно диффундирующего из объёма сформированного планарного композита к поверхности. Возможности и способы формирования и применения химически стойких тонкоплёночных покрытий на основе поверхностно модифицированных полимеров в медицинских, биологических, фармакологических и иных целях ранее были проанализированы в [28][29][30].…”
Section: Introductionunclassified